EVALUASI KINERJA BADAN LINGKUNGAN HIDUP DALAM UJI EMISI GAS BUANGAN KENDARAAN BERMOTOR DI KOTA PEKANBARU - Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
D armawati . NIM. 1201134501. Performance of Staffing Agency (BKD) in Pekanbaru on Civil Servant of the State. Guided by : Dr. Harapan Tua RFS, M.SiEmployee performance was the work of an individual within an organization. While the performance of the organization is the totality of the work that is within an organization. Performance assessment conducted by the staffing Agency in Pekanbaru doesn’t feel maximum due to the still much going on offense against the selection of mutations as well as work placement employees when mutation occurs. The purpose of this research is how the Agency's Staffing performance assessment (BKD) in Pekanbaru on Civil Servant to find out what factors that affect the performance of the Agency's Staffing (BKD) in Pekanbaru on Civil Servant.The concept of the theory used by the author is performance and mutations. The researchers used a qualitative descriptive study with research. In collecting the data, the author uses interview techniques and observations. The author uses the informant as a source of information and as a source of triagulasi techniques in the validity of the data.The results of this research show that the Agency's Staffing performance assessment (BKD) in Pekanbaru on Civil Apparatus was still not maximum, proved there are still deviations were found when the determination of mutational employees. Factors that influence the Agency's Performance in the Area of staffing (BKD) Pekanbaru on Civil Servant is a motivation factors and ability factors.Keywords: surveillance and Utilization and the use of parts of the road